THE EFFECT OF FINANCIAL MANAGEMENT PRACTICE ON ENTREPRENEURIAL PERFORMANCE OF MICRO, SMALL AND MEDIUM SCALE ENTERPRISES IN WEST OROMIA - Lemi, Kenenisa; Megersa, Reta; Bogale, Mekonnen (Journal of process management and new technologies, 2020)
Unemployment is becoming one of the basic challenges that all developing countries including Ethiopia are facing. To curve the problem and achieve their millennium development goal, such countries should focus on entrepreneurial activities that could enhance employment opportunity to unemployed youth. Micro, medium and small scale enterprises are the most enabling engine for entrepreneurial development of nations creating significant employment opportunities. But because of various factors, these enterprises are not performing as expected. This article therefore, analysed the effect of financial management practice on entrepreneurial performance in four west Oromia major towns mainly; Jimma, Mettu, Bunno Bedele and Nekemtie towns. The study utilized both primary and secondary data. The primary data was collected through self-administered questionnaire while secondary data was obtained from various sources. The proportionate to sample selection was applied to select samples. Descriptive statistics and binary logistic regression was applied to analyse data. The logistic regression indicated that accounting information system, financial reporting practice, financial education and literacy, working capital management, field of education of the owners/managers and manner of formation of the enterprises are significant factors affecting entrepreneurial performance in west Oromia. Hence, it is recommended that financial management practice has to be improved to enhance entrepreneurial performance of the micro, medium and small scale enterprises.